Effects of Epigallocatechin Gallate on Tert-Butyl Hydroperoxide-Induced Mitochondrial Dysfunction in Rat Liver Mitochondria and Hepatocytes - Mezera, Vojtech; Endlicher, Rene; Kucera, Otto; Sobotka, Ondrej; Drahota, Zdenek; Cervinkova, Zuzana (Oxidative medicine and cellular longevity, 2016)
Epigallocatechin gallate (EGCG) is a green tea antioxidant with adverse effects on rat liver mitochondria and hepatocytes at high doses. Here, we assessed whether low doses of EGCG would protect these systems from damage induced by tert-butyl hydroperoxide (tBHP). Rat liver mitochondria or permeabilized rat hepatocytes were pretreated with EGCG and then exposed to tBHP. Oxygen consumption, mitochondrial membrane potential (MMP), and mitochondrial retention capacity for calcium were measured. First, 50 μM EGCG or 0.25 mM tBHP alone increased State 4 Complex I-driven respiration, thus demonstrating uncoupling effects; tBHP also inhibited State 3 ADP-stimulated respiration. Then, the coexposure to 0.25 mM tBHP and 50 μM EGCG induced a trend of further decline in the respiratory control ratio beyond that observed upon tBHP exposure alone. EGCG had no effect on MMP and no effect, in concentrations up to 50 μM, on mitochondrial calcium retention capacity. tBHP led to a decline in both MMP and mitochondrial retention capacity for calcium; these effects were not changed by pretreatment with EGCG. In addition, EGCG dose-dependently enhanced hydrogen peroxide formation in a cell- and mitochondria-free medium. Conclusion. Moderate nontoxic doses of EGCG were not able to protect rat liver mitochondria and hepatocytes from tBHP-induced mitochondrial dysfunction.
Keywords: hepatocyty; Calcium; Male; Rats, Wistar; vápník; Mitochondria, Liver; terc-butylhydroperoxid; peroxid vodíku; mužské pohlaví; potkani Wistar; Hydrogen Peroxide; Hepatocytes; krysa rodu Rattus; spotřeba kyslíku; kultivované buňky; jaterní mitochondrie; Oxygen Consumption; Animals; zvířata; Rats; Catechin; membránový potenciál mitochondrií; Cells, Cultured; katechin; Membrane Potential, Mitochondrial; tert-Butylhydroperoxide